Effect of the COVID-19 pandemic on the proportion of physically active children and adults worldwide: A systematic review and meta-analysis - Chaabna, Karima; Chaabane, Sonia; Jithesh, Anupama; Doraiswamy, Sathyanarayanan; Mamtani, Ravinder; Cheema, Sohaila (Frontiers in Public Health, 2022)
Safety measures implemented to address the COVID-19 pandemic have had a profound impact on the mobility of people worldwide. We synthesized the global evidence on physical activity (PA) participation before and during the pandemic. We conducted a systematic review, searching PubMed, Embase, WHO Global literature on coronavirus disease, (between January and April 2022) and reference lists. Meta-analysis and meta-regression were conducted to quantitatively synthesize the data. Sixty-three primary studies were included. In children, the global pooled prevalence of PA was 46.4% before the pandemic, 40.6% during the pandemic before movement restriction, and 19.5% during movement restriction. A statistically significant decrease in prevalence was observed between the period before the pandemic and the period during which movement restriction was implemented (p-value<0.001). In adults, the global pooled prevalence (both sexes) decreased between the periods before the pandemic (64.7%) and during the pandemic when movement restriction was implemented (57.0%). Children had significantly lower odds to meet the WHO PA recommendation than adults during the period of COVID-19 movement restriction (OR=0.21, p-value= <0.001). Patient populations were less active than the general population and their PA levels decreased during the pandemic. Mental and physical health benefits of PA have been well demonstrated. Prioritizing PA in health campaigns and strategies is critical to address health issues exacerbated during this pandemic.